Clinical, dosimetric, and reporting considerations for Y-90 glass microspheres in hepatocellular carcinoma: updated 2022 recommendations from an international multidisciplinary working group - Salem, Riad; Padia, Siddharth A; Lam, Marnix; Chiesa, Carlo; Haste, Paul; Sangro, Bruno; Toskich, Beau; Fowers, Kirk; Herman, Joseph M; Kappadath, S Cheenu; Leung, Thomas; Sze, Daniel Y; et al. (Springer, 2023)
PURPOSE: In light of recently published clinical reports and trials, the TheraSphere Global Dosimetry Steering Committee (DSC) reconvened to review new data and to update previously published clinical and dosimetric recommendations for the treatment of hepatocellular carcinoma (HCC). METHODS: The TheraSphere Global DSC is comprised of health care providers across multiple disciplines involved in the treatment of HCC with yttrium-90 (Y-90) glass microsphere-based transarterial radioembolization (TARE). Literature published between January 2019 and September 2021 was reviewed, discussed, and adjudicated by the Delphi method. Recommendations included in this updated document incorporate both the results of the literature review and the expert opinion and experience of members of the committee. RESULTS: Committee discussion and consensus led to the expansion of recommendations to apply to five common clinical scenarios in patients with HCC to support more individualized efficacious treatment with Y-90 glass microspheres. Existing clinical scenarios were updated to reflect recent developments in dosimetry approaches and broader treatment paradigms evolving for patients presenting with HCC. CONCLUSION: Updated consensus recommendations are provided to guide clinical and dosimetric approaches for the use of Y-90 glass microsphere TARE in HCC, accounting for disease presentation, tumor biology, and treatment intent.
Keywords: Dosimetry; Hepatocellular carcinoma; Radioembolization; Yttrium-90; Radiology Nuclear Medicine and imaging; Journal Article